Neonatal Outcomes Differ after Spontaneous and Indicated Preterm Birth - Stout, Molly J.; Demaree, Devyn; Merfeld, Emily; Tuuli, Methodius G.; Wambach, Jennifer A.; Cole, F. Sessions; Cahill, Alison G. (American Journal of Perinatology, 2018)
Objective Preterm birth (PTB) at <37 weeks of gestation complicates 10% of pregnancies and requires accurate counseling regarding anticipated neonatal outcomes. PTB classification as spontaneous or indicated is commonly used to cluster PTB into subtypes, but whether neonatal outcomes differ by PTB subtype is unknown. We tested the hypothesis that neonatal morbidity differs based on subtype of PTB.Methods We performed a retrospective cohort study of live-born, non-anomalous preterm infants from 2004 to 2008. Spontaneous PTB was defined as PTB from spontaneous preterm labor or preterm rupture of membranes. Indicated PTB was defined as PTB from any maternal or fetal medical complication necessitating delivery. The primary outcome was a composite of early respiratory morbidity. Secondary outcomes included late composite respiratory morbidity and other neonatal morbidities.Results Of 1,223 preterm neonates, 60.9% were born after spontaneous PTB and 30.1% after indicated PTB. Composite early respiratory morbidity was significantly higher after indicated PTB versus spontaneous PTB (1.3, 95% confidence interval [CI] 1.2–1.4). Composite late respiratory morbidity (1.8, 95% CI 1.3–2.3) and neonatal death (2.8, 95% CI 1.5–5.1) were also significantly higher after indicated PTB versus spontaneous PTB.Conclusion Neonatal respiratory outcomes and death differ according to PTB subtype. PTB subtype should be considered while counseling families and anticipating neonatal outcomes after PTB.
Keywords: spontaneous preterm birth; indicated preterm birth; neonatal outcomes